La "guerre" des internautes - le hate dans la communication sur internet - Napieralski, Andrzej (Linguistica (Ljubljana), 2018)
War, the struggle between social groups with different persuasions, has not been kept from the internet, a technology which was supposed to bring people together in-stead of breaking them apart. In internet communication we often find a particular kind of discourse that can be seen as hate speech, which is a manifestation of intolerance, racism, xenophobia and ethnocentrism, while from a different prespective it appears as trolling, a supposedly playful way of ridiculing others and disturbing communication by breaking certain codes of behaviour. In order to define the attitudes of internet users who comment on various articles about politics, we propose using a transitional term, the hate, from American slang, although it also functions very well in Poland. This term refers to an attitude of criticism which is characteristic of the slander engaged in by the "enraged" users on the internet. Our study analyzes the discourse of internet users in the comments on political articles published in the two major French and Polish dailies, Le Monde (lemonde.fr) and Gazeta Wyborcza (gazeta.pl). The paper discusses some examples of hate from a discourse analytical perspective as well as in terms of the vocabulary used, which contains forms that are often offensive and at the same time creative. We also examine the degree to which hate varies between speakers from dif-ferent countries, and try to find out whether there are certain general trends in internet hate use due to globalisation.
Keywords: analiza diskurza; Francija; francoščina; internet; Poljska; poljščina; sociolingvistika; sovražni govor; spletni komentarji